Changes in Value Chains and Value Networks in the Bereavement Industry in Malaysia : A Case Study of NV Multi Asia - Law, Michele May Leng (2013)
The way the non-Muslim bereavement industry in Malaysia has changed over the last two decades since the inception of integrated end-to-end providers like NV Multi Asia Sdn. Bhd., or more widely recognised as the operator of Nirvana Memorial Parks and Nirvana Bereavement Centres has changed the competitive landscape in the country. Due to these changes, the incumbent players have had to react in order to remain relevant and competitive. This aim of this management project is to understand the strategies of the market leader in the industry in terms of the products and services it provides to customers. In order to achieve this, the Value Chain and Value Network of the firm are produced in order to study how all its value activities are organised, sourced, outsourced and coordinated. Further study was made on how the firm managed its innovation strategies and developed its core competencies. Questions were posed on what implications NV MULTI’s business strategies have had on the bereavement industry and whether the integration of products and services has been adopted by other competitors within the industry and what this means for the future of the industry and for NV MULTI’s competitive advantage. This study found that the other firms in the industry have in fact changed their own operations to offer more complete bereavement care services. The Value Chains and Value Networks have changed over the past two decades and the centuries-old practices and beliefs have begun to change resulting in industry players having to modernise and evolve accordingly.